Przemiany na obszarach wiejskich w opinii rolników gminy Olszanka w woj. mazowieckim - Kałuża, Halina (Changes in Country Regions in the Opinion of Farmers of the Olszanka Community in Mazowieckie Voivodship, 2005)
The aim of the paper was to show the questioned farmers opinion about their farms development possibilities. The research concentrates on individual farms of the community of Olszanka, which main source of income is the production of marketable agricultural goods. The purpose of the study is to present the role of market information for functioning of individual farms. It is shown that the main factors inhibiting proper functioning of individual farms are: lack of markets for agricultural products and high cost of means of production. The basic sources of market information are TV and the radio programmes. A large group of the farmers perceives their chance in the farms enlargement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 390-396